Meningeal Foam Cells and Ependymal Cells in Axolotl Spinal Cord Regeneration - Enos, Nathaniel; Takenaka, Hidehito; Scott, Sarah; Salfity, Hai V. N.; Kirk, Maia; Egar, Margaret W.; Sarria, Deborah A.; Slayback-Barry, Denise; Belecky-Adams, Teri; Chernoff, Ellen A. G. (Frontiers in Immunology, 2019)
A previously unreported population of foam cells (foamy macrophages) accumulates in the invasive fibrotic meninges during gap regeneration of transected adult Axolotl spinal cord (salamander Ambystoma mexicanum) and may act beneficially. Multinucleated giant cells (MNGCs) also occurred in the fibrotic meninges. Actin-label localization and transmission electron microscopy showed characteristic foam cell and MNGC podosome and ruffled border-containing sealing ring structures involved in substratum attachment, with characteristic intermediate filament accumulations surrounding nuclei. These cells co-localized with regenerating cord ependymal cell (ependymoglial) outgrowth. Phase contrast-bright droplets labeled with Oil Red O, DiI, and DyRect polar lipid live cell label showed accumulated foamy macrophages to be heavily lipid-laden, while reactive ependymoglia contained smaller lipid droplets. Both cell types contained both neutral and polar lipids in lipid droplets. Foamy macrophages and ependymoglia expressed the lipid scavenger receptor CD36 (fatty acid translocase) and the co-transporter toll-like receptor-4 (TLR4). Competitive inhibitor treatment using the modified fatty acid Sulfo-N-succinimidyl Oleate verified the role of the lipid scavenger receptor CD36 in lipid uptake studies in vitro. Fluoromyelin staining showed both cell types took up myelin fragments in situ during the regeneration process. Foam cells took up DiI-Ox-LDL and DiI-myelin fragments in vitro while ependymoglia took up only DiI-myelin in vitro. Both cell types expressed the cysteine proteinase cathepsin K, with foam cells sequestering cathepsin K within the sealing ring adjacent to the culture substratum. The two cell types act as sinks for Ox-LDL and myelin fragments within the lesion site, with foamy macrophages showing more Ox-LDL uptake activity. Cathepsin K activity and cellular localization suggested that foamy macrophages digest ECM within reactive meninges, while ependymal cells act from within the spinal cord tissue during outgrowth into the lesion site, acting in complementary fashion. Small MNGCs also expressed lipid transporters and showed cathepsin K activity. Comparison of 3H-glucosamine uptake in ependymal cells and foam cells showed that only ependymal cells produce glycosaminoglycan and proteoglycan-containing ECM, while the cathepsin studies showed both cell types remove ECM. Interaction of foam cells and ependymoglia in vitro supported the dispersion of ependymal outgrowth associated with tissue reconstruction in Axolotl spinal cord regeneration.